2022
DOI: 10.3390/nano12193275
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcome Pathways Associated with the Ingestion of Titanium Dioxide Nanoparticles—A Systematic Review

Abstract: Titanium dioxide nanoparticles (TiO2-NPs) are widely used, and humans are exposed through food (E171), cosmetics (e.g., toothpaste), and pharmaceuticals. The oral and gastrointestinal (GIT) tract are the first contact sites, but it may be systemically distributed. However, a robust adverse outcome pathway (AOP) has not been developed upon GIT exposure to TiO2-NPs. The aim of this review was to provide an integrative analysis of the published data on cellular and molecular mechanisms triggered after the ingesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 236 publications
1
5
0
Order By: Relevance
“…Recent studies investigating transgenerational effects have raised additional concerns regarding the potential impact on populations. These findings reinforce the European Food Safety Authority's decision to restrict the use of TiO2, emphasizing the need for caution in their application (12); Abrasives such as hydrated silica or calcium carbonate are used to help remove stains and plaque. Excessive or aggressive brushing with abrasive toothpaste can potentially harm tooth enamel; Artificial Colors are often on a list of ingredients in toothpaste to enhance their appearance.…”
Section: Introductionsupporting
confidence: 60%
“…Recent studies investigating transgenerational effects have raised additional concerns regarding the potential impact on populations. These findings reinforce the European Food Safety Authority's decision to restrict the use of TiO2, emphasizing the need for caution in their application (12); Abrasives such as hydrated silica or calcium carbonate are used to help remove stains and plaque. Excessive or aggressive brushing with abrasive toothpaste can potentially harm tooth enamel; Artificial Colors are often on a list of ingredients in toothpaste to enhance their appearance.…”
Section: Introductionsupporting
confidence: 60%
“…9,11,12 The nanomaterial has also been evidenced to cause DNA strand breaks, chromosomal damage, and gene mutation, and can induce epigenetic modifications. 8,10,[12][13][14] At higher concentrations, TiO 2 nanoparticles cause reproductive toxicity in both females and males, [15][16][17] and induce oxidative stress that leads to cell damage, inflammation, and adverse immune responses. 9,11,12,17 Systematic review and metaanalysis have demonstrated that TiO 2 nanoparticles disrupt the mammalian cell cycle in vitro, 18 and disturb glucose and lipid homeostasis in mice and rats.…”
Section: In Vitro and In Vivo Effects Of Tio 2 Nanoparticlesmentioning
confidence: 99%
“…8,10,[12][13][14] At higher concentrations, TiO 2 nanoparticles cause reproductive toxicity in both females and males, [15][16][17] and induce oxidative stress that leads to cell damage, inflammation, and adverse immune responses. 9,11,12,17 Systematic review and metaanalysis have demonstrated that TiO 2 nanoparticles disrupt the mammalian cell cycle in vitro, 18 and disturb glucose and lipid homeostasis in mice and rats. 11,12 The nanomaterial has also been found to impact the digestive tract, increasing chronic intestinal inflammation and disorders of the intestinal barrier, and disrupting the normal functions of the gastrointestinal tract.…”
Section: In Vitro and In Vivo Effects Of Tio 2 Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been discovered that titanium dioxide, which is accepted to be ingested orally by young children between the ages of 2 and 6, is absorbed via the intestines and causes biological harm at the cellular and molecular level (Rompelberg et al 2016). Since the concentration of titanium dioxide, which can be ingested not only through toothpaste but also through numerous food products (milk, cream, coffee, gum, sauce), can reach very high levels in the body, it is advantageous to avoid using it in toothpastes in order to minimize exposure (Rolo et al 2022). It is notable that this substance is present in nearly two-thirds of toothpastes marketed in our country.…”
mentioning
confidence: 99%